Feasibility Investigation on the N2 Injection Process to Control Water Coning in Edge Water Heavy Oil Reservoirs - Zheng, Wei; Feng, Yabin; Tan, Xianhong; Yang, Renfeng; Liu, Huiqing; Xie, Haojun; Wang, Taichao (Frontiers in Earth Science, 2022)
N2 injection process is a potential technique to control the water coning behavior in heavy oil reservoirs. In this paper, by using the methods of experiment and numerical simulation, the N2 injection process for controlling the edge water coning behavior is investigated. First, through a visual fluid flow experimental device, the flow behavior of N2-water in porous media is discussed. And the effect of temperature, pressure and injection rate are studied. Then, based on the experimental results, aiming at an actual edge water heavy oil reservoir, a reservoir simulation model is developed. Thus, the water coning behavior of edge aquifer is systematically studied. And two novel indicators are proposed to evaluate the water coning behavior. Then, A series of numerical models are developed to investigate the performance of N2 injection process in edge water heavy oil reservoirs after water coning. And the adaptability and the optimal operation parameters are analyzed. Results indicate that under the effect of porous media, N2 can cut into a series of small gas bubble. It is a typical dispersed phase and can effectively plug the water coning path. Compared with pressure and injection rate, temperature is a more sensitive factor to affect the pugging performance of N2. From the simulation results, it is observed that the permeability, water/oil ratio and distance between well and aquifer can significantly affect the performance of water coning behavior. N2 injection process can effectively control the edge water coning and improve the CSS performance. Furthermore, from the simulation results, it is found that the optimal operation parameters for a N2 injection process is that the total N2 injection volume should be higher than 6000 m3 within one operation cycle and the optimal N2 injection rate should be lower than 700 m3/d. This investigation further clarifies the mechanisms of N2 injection process to control the water coning behavior in heavy oil reservoirs. It can provide a useful reference for the EOR process of the heavy oil reservoirs with edge water.